Ruddlesden–Popper Perovskites: Spontaneous Formation of Nanocrystals in Amorphous Matrix: Alternative Pathway to Bright Emission in Quasi‐2D Perovskites (Advanced Optical Materials 19/2019). Issue 19 (6th October 2019) - Liu, Fangzhou; Chan, Christopher Chang Sing; Ma, Chao; Tam, Ho Won; Leung, Tik Lun; Lin, Jingyang; Djurišić, Aleksandra B.; Wong, Kam Sing; Popović, Jasminka; Ng, Alan Man Ching; Chan, Wai Kin; Chen, Wei; et al.
Abstract : The formation of nanocrystals in quasi‐2D Ruddlesden–Popper perovskite can be spontaneously induced by appropriately timed anti‐solvent treatment, as reported by Aleksandra B. Djurišić, Kam Sing Wong, and co‐workers in article number1900269 . Only nanocrystals with n = 4 phase are detected, different from commonly obtained mixtures of different phases. The formation of nanocrystals in a disordered matrix results in a significant enhancement of the light emission due to defect passivation.